NILAI BUDAYA DALAM CERITA RAKYAT JAMBU LIPO - Putri Mayang Sari (Universitas Andalas, 2012)
This article describes analysis result on cultural contents of Jambu Lipo folktales. Jambu Lipo is one of kingdoms in Minangkabau teritory. These folktales analyzed with Kluckhohn and Srtodtbeck theory. The result shows relationship between human and nature, human and their jobs, and between human and human.